2010
DOI: 10.2169/internalmedicine.49.3107
|View full text |Cite
|
Sign up to set email alerts
|

The Insulin Sparing Effect of Telmisartan in a Case of Type 2 Diabetes Mellitus Associated with Schizophrenia under Treatment of Risperidone

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The insulin-sparing effect of telmisartan in a case of type 2 diabetes associated with risperidone-treated SZ was also reported. Switching from candesartan to telmisartan dramatically improved glycemic control (HbA1c levels decreased from 8.3 % to 6.0 % in 6 months with reduction in insulin requirement from 62 U/day to 46 U/day in 6 months and to 18 U/day in 15 months), with significant weight reduction (from 81 kg to 65 kg in 15 months) with SZ medication not changed and without remarkable lifestyle modification [132]. Another study, conducted on group of SZ patients treated with olanzapine, showed that ARBs add-on treatment resulted in improved insulin sensitivity and attenuated insulin resistance [133].…”
Section: Psychotic Disordersmentioning
confidence: 99%
“…The insulin-sparing effect of telmisartan in a case of type 2 diabetes associated with risperidone-treated SZ was also reported. Switching from candesartan to telmisartan dramatically improved glycemic control (HbA1c levels decreased from 8.3 % to 6.0 % in 6 months with reduction in insulin requirement from 62 U/day to 46 U/day in 6 months and to 18 U/day in 15 months), with significant weight reduction (from 81 kg to 65 kg in 15 months) with SZ medication not changed and without remarkable lifestyle modification [132]. Another study, conducted on group of SZ patients treated with olanzapine, showed that ARBs add-on treatment resulted in improved insulin sensitivity and attenuated insulin resistance [133].…”
Section: Psychotic Disordersmentioning
confidence: 99%
“…To the Editor I read with interest the case report "The insulin sparing effect of telmisartan in a case of type 2 diabetes mellitus associated with schizophrenia under treatment of risperidone", recently published by Yamaguchi and Tsutsumi (1). A striking aspect of the case was the loss of 16 kg in 15 months without remarkable life-style modification.…”
mentioning
confidence: 99%